SYSTEM GALILEO WILL HELP TO REVITALISE THE RAILWAYS (Perner's Contacts, 2006)
The article deals with the study, which is based on the expertise of the UIC work group GALILEO applications for rail. The power of using the satellite navigation technology in the railway system results from its combination with other technologies. The GALILEO technology provides an impressive potential for applications in the railway system.
Keywords: standards; integration; modularity; flexibility of the railway system